Temozolomide and etoposide combination for the treatment of relapsed osteosarcoma. (28th May 2020) - Akazawa, Ryo; Umeda, Katsutsugu; Saida, Satoshi; Kato, Itaru; Hiramatsu, Hidefumi; Sakamoto, Akio; Arakawa, Yoshiki; Sumiyoshi, Shinji; Okamoto, Takeshi; Moritake, Hiroshi; Adachi, Souichi; Takita, Junko
Abstract: The prognosis of patients with relapsed osteosarcoma is extremely poor and the optimal treatment remains to be identified. Here, we retrospectively analysed the clinical outcomes of nine patients with relapsed osteosarcoma treated with temozolomide/etoposide. Of the two patients who received temozolomide/etoposide as palliative therapy for unresectable tumours, one remained alive with stable disease for >4 years. The remaining seven patients received temozolomide/etoposide as adjuvant therapy following resection of relapsed metastatic disease; of these, one was free from disease for 41 months. Potentially beneficial effects were observed in two of three O6-methylguanine-DNA methyltransferase protein-negative patients, whereas all five O6-methylguanine-DNA methyltransferase-positive patients experienced subsequent relapse. None of the patients experienced severe adverse effects requiring hospitalization. Temozolomide/etoposide is a feasible candidate as salvage therapy for relapsed osteosarcoma. Further studies are needed to verify the utility of O6-methylguanine-DNA methyltransferase protein expression as a biomarker for predicting the response to this treatment. Abstract : Combination treatment with temozolomide and etoposide showed beneficial therapeutic effects in two of nine patients with relapsed osteosarcoma, both were negative for O6-methylguanine-DNA methyltransferase protein expression.